DNA fingerprinting and minisatellite variation of swans - Meng, Anming (1990)
Genetic variation in natural populations of four species of swans (Cygnus bewickii, Cygnus olor, Cygnus buccinator and Cygnus cygnus) has been investigated by examining minisatellite loci using human DNA fingerprinting probes pSPT19.6 and pSPT18.15. It has been found that swan minisatellites are highly variable. However, the degree of variation depends on the population structure and species. Bewick's Swans at Slimbridge have the highest degree of minisatellite variation, Whooper Swans at Caerlaverock come second, and then Mute Swans, and Trumpeter Swans in Montana. Comparative study of DNA fingerprints among populations and among species suggested that swan minisatellites are subject to specific as well as population differentiation, although the function of minisatellites remains an unsolved mystery.